(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of depression among Pemphigus patients undergoing Glucocorticosteroids treatment at the clinical departments of Ho Chi Minh city Hospital of Dermato-Venereology. Methods: A cross-sectional study was conducted on 140 patients with clinically and histologically confirmed Pemphigus. Results: Among the 140 patients, 109 were diagnosed with Pemphigus vulgaris and 31 with Pemphigus foliaceus. Female patients predominated (61.4%). Most patients had mild to moderate disease severity according to the PDAI score (65% and 33.6%, respectively). A relatively high prevalence of depression was observed (43.6%), with the majority classified as mild depression (38.6%). No patients were diagnosed with severe depression. Conclusion: Comprehensive dermatological management may contribute to reducing the severity of depression in patients with Pemphigus.